2010
DOI: 10.1016/j.jtcvs.2010.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of secondary tricuspid valve regurgitation: Annulus, commissure, or leaflet procedure?

Abstract: Rigid prosthetic ring annuloplasty, standard or 3-dimensional, provides early and sustained reduction of tricuspid regurgitation secondary to left-sided valve disease without need for an additional leaflet procedure. However, results are imperfect, possibly because other anatomic levels (subvalvular, papillary muscle, and right ventricular) contributing to its pathophysiology are unaddressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
168
1
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(185 citation statements)
references
References 24 publications
7
168
1
9
Order By: Relevance
“…Ghoreishi [28] showed that the rigid three-dimensional ring could be the most reliable and durable treatment for FTR. This ring annuloplasty provides an early and sustained reduction of TR secondary to LVD, which has been reported by Navia [29]. In our series, the recurrent rates were significantly lower in the Rigid Group than in the Flexible Group postoperatively.…”
Section: Tablesupporting
confidence: 76%
“…Ghoreishi [28] showed that the rigid three-dimensional ring could be the most reliable and durable treatment for FTR. This ring annuloplasty provides an early and sustained reduction of TR secondary to LVD, which has been reported by Navia [29]. In our series, the recurrent rates were significantly lower in the Rigid Group than in the Flexible Group postoperatively.…”
Section: Tablesupporting
confidence: 76%
“…Navia et al (12) and Izutani et al (13) reported a lower rate of recurrent TR with a rigid annuloplasty ring compared with a flexible ring. On the contrast, Pfannmüller et al (14) reported a higher rate of annuloplasty dehiscence after the implantation of a rigid ring.…”
Section: Original Articlementioning
confidence: 97%
“…Tricuspid annuloplasty (TA) is currently recommended for the treatment of significant TR3, 4 and has been increasingly performed over the past decade 5. Although TA has shown a satisfactory outcome in the short term, postoperative residual significant TR and mortality remain high during long‐term follow‐up 6, 7. Accurate preoperative risk evaluation is essential to identify patients at high risk and improve clinical outcome.…”
Section: Introductionmentioning
confidence: 99%